The Effect of Lithium Disilicate Ceramic Surface Neutralization on Wettability of Silane Coupling Agents and Adhesive Resin Cements - Ravikumar Ramakrishnaiah; Abdulaziz Abdullah Alkheraif; Darshan Devang Divakar; Khuloud Fahad Alghamdi; Jukka Pekka Matinlinna; Christie Ying Kei Lung; Sunil Cherian; Pekka Kalevi Vallittu (Springer Netherlands, 2022)
This in vitro study was aimed to evaluate the possible changes in wettability of an etched glass ceramic surface to silane primers, adhesive resin and resin cement when the surface had been neutralized by a special neutralizing agent after etching. Rectangular shaped specimens were cut from the CAD blocks of an e-max lithium disilicate glass ceramic, cut specimens were sequentially polished and ultrasonically cleaned. All the specimens were etched for 20 s with 5% hydrofluoric acid and ultrasonically cleaned. Specimens were randomly assigned to one control group (without neutralization) and one treatment group (with neutralization) having 20 specimens each. The specimens of each group were further divided into two subgroups having 10 specimens each and tested to determine the effect of neutralizing agent on wettability of experimental and commercial silanes. Each subgroup specimen was tested for wettability to adhesive resin and commercial resin cement. Data were analyzed using two-way ANOVA. Neutralizing the ceramic surface did not show a significant effect on wettability to the silanes and the resin based materials, but the experimental silane showed better wettability than the commercial silane. The adhesive resin had statistically significant lower contact angle (high wettability) values than the commercial resin cement. The results of the current study suggested that the neutralizing agent did not have an impact on the wettability of the etched ceramic. However, there were differences in wetting properties of the silane primers, and adhesive resin versus resin composite luting cements.